Design of fatigue testing machine for small wind turbines - Hemici, Youcef (Echahid Hama Lakhdar University of Eloued, 2023)
"Wind energy is considered one of the most important renewable energy sources. For this reason, researchers and experts have focused greatly on developing and improving it in all aspects. One of the challenges that receives special attention is the phenomenon of fatigue, which represents a major challenge in the field of wind energy and requires intensive efforts to address it and deal with its impact. Based on previous research and studies, and as a way to materialize the idea, we designed a small device in this note to measure the voltage and bearing of wind turbine blades. This device allows results to be obtained by applying varying intensity forces to the studied blade, taking into account the materials and materials used in the manufacturing process. We tested the machine through simulation, which allowed us to apply different loads to study stresses and displacements. To achieve this, we followed a few steps, including masking the parts that are constantly changing, which allowed us to monitor the stresses on the fixed parts. Deformation is also one of the causes that cause damage to mechanical parts and cause them to lose their functions. " "طاقة الرياح تعتبر واحدة من أهم مصادر الطاقة المتجددة. لهذا السبب، ركز الباحثون والخبراء بشكل كبير على تطويرها وتحسينها من جميع الجوانب. واحدة من التحديات التي تلقي اهتماماً خاصًا هي ظاهرة التعب، التي تمثل تحديًا كبيرًا في مجال طاقة الرياح وتتطلب جهودًا مكثفة لمعالجتها والتعامل مع تأثيرها. باستنادًا إلى البحوث والدراسات السابقة، وكوسيلة لتجسيد الفكرة، قمنا بتصميم جهاز صغير في هذه المذكرة لقياس الجهد وتحمل شفرات توربينات الرياح. يتيح هذا الجهاز الحصول على نتائج من خلال تطبيق قوى متنوعة بكثافة على الشفرة المدروسة، مع مراعاة الخامات والمواد المستخدمة في عملية التصنيع. قمنا بإجراء اختبار على الالة من خلال المحاكاة، والتي سمحت لنا بتطبيق أحمال مختلفة لدراسة الضغوط والازاحة. لتحقيق ذلك، اتبعنا بعض الخطوات، بما في ذلك إخفاء الأجزاء التي تتعرض للتغيير المستمر، مما سمح لنا بمراقبة الضغوط على الأجزاء الثابتة. كما أن التشوه يعتبر واحداً من الأسباب التي تسبب ضررًا للأجزاء الميكانيكية وتسبب في فقدان وظائفها. "
مذكرات ماستر تخصص الطاقات المتجددة في الميكانيك
Keywords: Design, fatigue, wind turbines; تصميم توربينات الرياح التعب